Factors Affecting the Revenue of Air Asia Berhad During Covid-19 Pandemic - Singh, Padmalini; Sinha, Rupesh; A/P Nagenthran, Yarshinni; Teoh, Kok Ban; Yong, Hui Yee; Wijaya, Shahwatul Hajjah Islamia; Aryani, Dwi Nita; Singh, Himanshi; Das, Abhijit; Dabeer, Sindhu L (AIBPM Publisher, 2021)
Air Asia Berhad is very well-known as the low-cost airline, the headquarter is located in Kuala Lumpur, Malaysia. It is the largest airline in Malaysia by fleet size and destinations. It has consistently been named as the world’s best low-cost carrier for 11 years by Skytrax. Low-cost plan helps the company to earn profit in fact. However, in 2020, the revenue of Air Asia Berhad has decreased terribly due to the Covid-19 pandemic. Covid-19 pandemic began to spread in the final week of January 2020 at Malaysia and until this moment in time, the whole world is still facing the pandemic. It is also known as Coronavirus which can be spread through air and close contact. Due to Covid-19 pandemic, the passengers carried has been decreased by 74% by January to December 2020 on comparison with January to December 2019 which directly implies less revenue generation. Furthermore, many of the staff has been laid off. The particular aim for this research is to determine the factors affecting the revenue generation of the company during Covid-19. Google form was used to collect the needed information for this research. With the collected data through the study, it was found out that restrictions in travelling, paucity of passengers and high number of workers in the company are the main factors giving the current impact to the company’s revenue.